The lost girls of Paris [compact disc, unabridged] - Jenoff, Pam (Harper Audio, Inc., 2019)
Grace Healey is rebuilding her life after losing her husband during the war. One morning while passing through Grand Central Terminal on her way to work, she finds an abandoned suitcase tucked beneath a bench. Unable to resist her own curiosity, Grace opens the suitcase, where she discovers a dozen photographs, each of a different woman. In a moment of impulse, Grace takes the photographs and quickly leaves the station. Grace soon learns that the suitcase belonged to a woman named Eleanor Trigg, leader of a ring of female secret agents who were deployed out of London during the war. Twelve of these women were sent to Occupied Europe as couriers and radio operators to aid the resistance, but they never returned home, their fates a mystery. Setting out to learn the truth behind the women in the photographs, Grace finds herself drawn to a young mother turned agent named Marie, whose daring mission overseas reveals a remarkable story of friendship, valor, and betrayal.